A Term Pregnancy With Placental Entrapment At Uterus Cornu Due To Septate Uterus With Double Cervix And Longitudinal Vaginal : A Rare Case Report With Incidental Anomaly Finding - Hendryan, Derevie; Munizar, Munizar; Salmiah, Salmiah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Uterine malformations or Mullerian anomalies are anatomical abnormalities found in the uterus, cervix and vagina. This disorder is caused by problems with the development of the Mullerian duct during fetal growth, affecting about 4.3% of infertile women and 3.5% of infertile women. This disorder increases the risk of obstetrics, which leads to a higher incidence of miscarriage, premature birth (ranging from 17.44% to 33.3% in the case of the uterine septum), malpresentation, and a decrease in the live birth rate. Case Presentation : Mrs. 27 years old G2P0A1. The patient comes to the poly for the re-control of her pregnancy, the patient plans the Elective Section of the cesarean section a.i the location of the bond. Her menstrual cycle is regular, BMI is normal, has no history of surgery, has a 4-year history of infertility. The history of dyspareunia is denied, dysmenorrhea or chronic abdominal pain is denied. Obstetric examination was obtained at TFU 30, left back, DJJ: 159 x/i. It feels round, hard and bouncy in the lower right. The inspector's examination found 2 vaginal openings. Intraoperatively born a baby girl 2600 grams A/S 8/9 placenta sticky. An externalization of the uterus appears to bulging the placenta in the corneus sinistra. The placenta is removed manually and nausica sutures are performed in the cornea to overcome uterine hypotonia. Discussion : Anomalies of female genetic organs can be caused by several mechanisms that can be abbreviated as CAFÉ which stands for (Canalization, Agenesis, Fusion, Embryonic rest). Anomalies in the female genetic organs are caused by defects in the lateral and vertical fusion processes of the urogenital sinuses and Muller's ducts. The fusion process (fusion) of the right and left Muller ducts will be completed at 12 weeks of gestation. Meanwhile, the canalization process will be completed at 5 months of gestation. Failure of vertical fusion between the Muller duct and the urogenital sinus will cause disorders of the canalization of the genetical organs. Furthermore, failure to perform lateral fusion will lead to organ duplication. Impaired resorption will result in the formation of a septum. The patient also experiences placental retention. Conclusion: Uterine abnormalities or also known as uterine anomalies can increase the risk of miscarriage, premature birth, and fetal malpresentation. Often undiagnosed for many years, a cesarean section can provide unique diagnostic opportunities, as well as reduce additional risks.